Factors affecting stability and infectivity of SARS-CoV-2 - Chan, K-H.; Sridhar, S.; Zhang, R.R.; Chu, H.; Fung, A.Y-F.; Chan, G.; Chan, J.F-W.; To, K.K-W.; Hung, I.F-N.; Cheng, V.C-C.; Yuen, K-Y. (The Journal of hospital infection, 2020)
In late 2019, a novel human coronavirus – severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) – emerged in Wuhan, China. This virus has caused a global pandemic involving more than 200 countries. SARS-CoV-2 is highly adapted to humans and readily transmits from person-to-person. To investigate the infectivity of SARS-CoV-2 under various environmental and pH conditions. The efficacies of various laboratory virus inactivation methods and home disinfectants against SARS-CoV-2 were investigated. The residual virus in dried form or in solution was titrated on to Vero E6 cells on days 0, 1, 3, 5 and 7 after incubation at different temperatures. Viral viability was determined after treatment with various disinfectants and pH solutions at room temperature (20–25oC). SARS-CoV-2 was able to retain viability for 3–5 days in dried form or 7 days in solution at room temperature. SARS-CoV-2 could be detected under a wide range of pH conditions from pH 4 to pH 11 for several days, and for 1–2 days in stool at room temperature but lost 5 logs of infectivity. A variety of commonly used disinfectants and laboratory inactivation procedures were found to reduce viral viability effectively. This study demonstrated the stability of SARS-CoV-2 on environmental surfaces, and raises the possibility of faecal–oral transmission. Commonly used fixatives, nucleic acid extraction methods and heat inactivation were found to reduce viral infectivity significantly, which could ensure hospital and laboratory safety during the SARS-CoV-2 pandemic.